Impact of ultrasound combined with ultrahigh pressure pretreatments on color, moisture characteristic, tissue structure, and sensory quality of freeze‐dried strawberry slices. Issue 3 (2nd February 2021) - Zhang, Lihui; Qiao, Yu; Wang, Chao; Liao, Li; Shi, Defang; An, Kejing; Hu, Jianzhong
Abstract: The effect of pretreatments (ultrasound (US), ultrahigh pressure (UHP), and the combination (US‐UHP)) on the color, moisture, tissue structure, and sensory quality of strawberry slices were investigated. US, UHP, and US‐UHP pretreatment significantly increased the anthocyanin content and redness in the center section of strawberry slices, resulting in the increase of anthocyanin content by 0.62 mg/g, 1.01 mg/g, and 3.09 mg/g, respectively. Compared to the control, all pretreatments decreased the moisture content, and transverse relaxation time. The distribution of water become more uniform after pretreatment, and US, UHP, and US‐UHP pretreatment decreased the total energy consumption by 12.52%, 29.90%, and 42.39%, respectively. The changes observed on the structure of the strawberry explained the effects of these pretreatments on the water diffusion and color change. Practical applications: Freeze vacuum‐dried fruit slices is currently increasingly popular with modern consumers due to their long shelf life and nutritional values with an attractive crispy taste. However, freeze vacuum drying is a long drying time, high energy, and cost‐intensive process. The application of US‐UHP technology is an effective method before food drying since the use of US‐UHP pretreatment is used, as well shorter drying times are obtained, and consequently, lower the total energy consumption. The US‐UHP improves color and sensory properties of strawberry slices, which can serve as a pretreatment method to process freeze vacuum‐dried strawberry slices.